The Effect 0f Combined Pursed Lip Breathing and Peppermint Aromatherapy on the Respiratory Status of Coronary Heart Disease Patients - Lilik Sriwiyati; Abu Bakar; Herdina Maryanti (Indonesian Journal of Global Health Research, 2026)
Since cardiovascular disease is the world's biggest cause of death, it poses a threat to the entire planet. Common signs of cardiac issues include shortness of breath, changes in breathing patterns, breathing frequency, and breathing depth. Patients with coronary heart disease require intervention to enhance their respiratory condition since respiratory issues can negatively impact their quality of life. It is necessary to demonstrate how a combination therapy of pursed lip breathing (PLB) and peppermint aromatherapy affects the respiratory condition of individuals with coronary heart disease. Only one intervention—breathing exercises to lessen dyspnea or aromatherapy to lessen tension and anxiety in individuals with coronary heart disease—has been offered by prior research. In order to enhance the respiratory status of patients with coronary heart disease, this study combines pursed lip breathing with peppermint aromatherapy interventions. Purposive sampling strategies were used to split a sample of 44 coronary heart disease patients into an intervention group and a control group for the quasi-experimental study design. Stopwatches, oximeters, and observation sheets were the tools utilized. The Mann Whitney U Test and the Wilcoxon Signed Rank Test were used for statistical analysis. Following the intervention, the data demonstrated an increase in oxygen saturation and a decrease in respiratory rate. Both the rise in oxygen saturation and the decrease in respiratory rate were greater in the intervention group compared to the control group. The combination therapy of pursed lip breathing and peppermint aromatherapy had an impact on respiratory status, according to the statistical test findings, which indicated a p-value < 0.05. In patients with coronary heart disease, the combination therapy of pursed lip breathing and peppermint aromatherapy was found to significantly lower respiratory rate and raise oxygen saturation.